2005
DOI: 10.1002/gps.1397
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine does not enhance cognition in non-agitated and non-psychotic patients with mild to moderate Alzheimer's dementia

Abstract: In this 26-week study non-psychotic/non-agitated patients with Alzheimer's disease treated with olanzapine experienced significant worsening of cognition as compared to placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 19 publications
(16 reference statements)
2
33
2
Order By: Relevance
“…Results of the overall treatment comparisons in the present study differ from findings in a study of Alzheimer's dementia patients without BPSD in which olanzapine-treated patients with moderately severe baseline cognitive impairment experienced significant cognitive decline (Kennedy et al, 2005). The reason for differences in cognitive vulnerability between dementia patients with BPSD and those without BPSD during olanzapine treatment is not readily apparent.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Results of the overall treatment comparisons in the present study differ from findings in a study of Alzheimer's dementia patients without BPSD in which olanzapine-treated patients with moderately severe baseline cognitive impairment experienced significant cognitive decline (Kennedy et al, 2005). The reason for differences in cognitive vulnerability between dementia patients with BPSD and those without BPSD during olanzapine treatment is not readily apparent.…”
Section: Discussioncontrasting
confidence: 60%
“…In one of these trials, significant cognitive improvement was reported in patients who received olanzapine 2.5 mg/d (De Deyn et al, 2004). The potential to improve cognition was explored further in a trial in dementia patients without BPSD (Kennedy et al, 2005). In that study, patients who received olanzapine experienced a significant decline in cognition, which was greatest in those with more severe cognitive impairment at baseline.…”
Section: Introductionmentioning
confidence: 96%
“…10 Studies of the atypical olanzapine have reported mixed results, ranging from no effect 11 to enhancing 12 or worsening cognition. 13 RCTs using risperidone for neuropsychiatric symptoms in dementia have, however, consistently found it to be effective without cognitive side effects. [14][15][16] Two recent systematic reviews report only a modest improvement in neuropsychiatric symptoms from atypicals 17 and none from typical antipsychotics.…”
mentioning
confidence: 99%
“…It has been hypothesized in the past that olanzapine may benefit cognition through antagonism of cholinergic neuron receptors M2, 5HT3, and 5HT6. Multiple short-term clinical trials in AD have shown a worsening of cognition when treated with atypical antipsychotics [125,126]. …”
Section: Resultsmentioning
confidence: 99%